Specific Follicular Helper T Cell Signature in Takayasu Arteritis. Issue 7 (19th May 2021) - Desbois, A. C.; Régnier, P.; Quiniou, V.; Lejoncour, A.; Maciejewski‐Duval, A.; Comarmond, C.; Vallet, H.; Rosenzwag, M.; Darrasse‐Jèze, G.; Derian, N.; Pouchot, J.; Samson, M.; et al.
Abstract : Objective: Our aim was to compare transcriptome and phenotype profiles of CD4+ T cells and CD19+ B cells in patients with Takayasu arteritis (TAK), patients with giant cell arteritis (GCA), and healthy donors. Methods: Gene expression analyses, flow cytometry immunophenotyping, T cell receptor (TCR) gene sequencing, and functional assessments of cells from peripheral blood and arterial lesions from TAK patients, GCA patients, and healthy donors were performed. Results: Among the most significantly dysregulated genes in CD4+ T cells of TAK patients compared to GCA patients (n = 720 genes) and in CD4+ T cells of TAK patients compared to healthy donors (n = 1, 447 genes), we identified a follicular helper T (Tfh) cell signature, which included CXCR5, CCR6, and CCL20 genes, that was transcriptionally up‐regulated in TAK patients. Phenotypically, there was an increase in CD4+CXCR5+CCR6+CXCR3− Tfh17 cells in TAK patients that was associated with a significant enrichment of CD19+ B cell activation. Functionally, Tfh cells helped B cells to proliferate, differentiate into memory cells, and secrete IgG antibodies. Maturation of B cells was inhibited by JAK inhibitors. Locally, in areas of arterial inflammation, we found a higher proportion of tertiary lymphoid structures comprised CD4+, CXCR5+, programmed death 1+, and CD20+ cells in TAK patients compared to GCA patients. CD4+CXCR5+ T cells in the aortas of TAK patients had an oligoclonal α/β TCR repertoire. Conclusion: We established the presence of a specific Tfh cell signature in both circulating and aorta‐infiltrating CD4+ T cells from TAK patients. The cooperation of Tfh cells and B cells might be critical in the occurrence of vascular inflammation in patients with TAK.